Rural development in Haryana: Gender dynamics, infrastructure, and agricultural progress - Kumar, Vipin; Khunger, Sameesh (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
This study investigates the multifaceted dynamics of rural development in Haryana, emphasizing the interconnections between gender, infrastructure, agriculture, and entrepreneurship. Despite ongoing progress, significant challenges persist, particularly in ensuring equitable access to economic opportunities and essential services. This research employs a mixed-methods approach, integrating a quantitative survey of 250 respondents with qualitative interviews involving 20 key stakeholders. Findings indicate that while gender-based income disparities are not statistically significant, inequalities in access to economic resources and opportunities remain a critical concern. Infrastructure satisfaction levels vary, with pressing deficiencies identified in healthcare and education sectors. Participation in skill development programs emerges as a key factor in improving livelihoods, though notable gaps exist in reaching marginalized communities and older populations. Furthermore, entrepreneurial growth is constrained by barriers related to capital access and regulatory complexities. Unlike previous studies that have examined these factors in isolation, this research adopts a holistic approach, providing a more comprehensive understanding of the rural development landscape in Haryana. The findings underscore the necessity of inclusive and adaptive policies, focusing on strengthening infrastructure, promoting equitable skill development, and facilitating entrepreneurship. Additionally, integrating environmental sustainability into development planning is crucial to ensuring long-term, equitable progress in rural Haryana.